?POPULATION DYNAMICS OF COlLI A DUSSUMIERI FROM THE KUTUBDIA CHANNEL OF BANGLADESH COASTAL WATER (Biological Sciences - PJSIR, 1999)
Elefan I and Elcfan II were used to estimate the population parameters and length-frequency-based cohort analysis of Coiliadussumieri,collected from Kutubdia channel of Bangladesh coastal water. The VonBertalanffy growth parameters Leeand K for the species were 16.80 em and 1.30 year I,respectively. The annual rate ofM,F and Z were found to be 2.49, 2.30 and 4.79, respectively. The exploitation rate (E) was estimated as 0.48. This fish was recruited in the fishery during April-June and August-October. Peaks appeared in the months of May and September. Ema • was found to be 0.602. From the analysis Coilia dussumieri showed below optimum fishing pressure (i.e. E